FERRAMENTAS VISUAIS PARA PLANEJAMENTO E CONTROLE DA PRODUÇÃO HIERARQUIZADO - Utzig, Helena; Zani, Carolina Melecardi; Rocha, Cecilia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Construction is a process beyond the transformation of inputs into products. Considering the steps involved (processing, handling, inspection, and material waiting) there are waste generated in all stages, and it cannot be avoided. However, one way to minimize it is to plan and control construction. This paper aims to propose tools that improve the reliability of the planning, as well as to facilitate the communication of it to the users. This investigation was structured in four stages: (i) literature review; (ii) partnership with a construction company willing to implement lean production (iii) implementation of short, medium and long term planning; (iv) analysis of indicators and development of new tools. As a result, the proposed tools are: (i) indicator of unplanned but realized activities compared to the planned activities; (ii) chart of the reasons for non-compliance activities; (iii) layout drawing that shows the activities planned on the week; (iv) a method to develop the balance line for long-term planning.